Spot Activity of AK Her Binary Star - Murad, Ismail Musa; Ababakr, Karim Mahmood (Al-Nahrain Journal of Science, 2012)
In this investigation B and V filters light curves of the AK Her are presented. Their light curves notice O’Connell effect phenomenon in which the level of the primary maxima peaks being higher than that of the secondary ones or contrarily in both filters. Photometric solutions were carried out by using the latest version (2003) of the W-D program; the present light curves are analyzed. The spot model has been applied to fit the asymmetric light curves in order to explain the O’Connell effect. The explanation of the O’Connell effect by spot model of AK Her binary carried out for the first time by cool spot on the primary component and the spot parameters of such system have been determined. It has been observed that by changing only the spot parameters, the model light curves can fit the observed light curves. This indicates that the variation of the spot location, size and its temperature is the main reason for changing the shape of light curves. The spot effect has been calculated to compare how much the light curve is distorted by the star spot; also the spot area has been calculated. It is found that the system is over-contact of A-subtype. From our data analysis, the fundamental orbital, physical and geometrical parameters were determined, and the absolute parameters have been determined.